2017
DOI: 10.1016/j.ymgmr.2017.05.010
|View full text |Cite
|
Sign up to set email alerts
|

Early hematopoietic stem cell transplantation in a patient with severe mucopolysaccharidosis II: A 7 years follow-up

Abstract: Mucopolysaccharidosis type II (MPS II - Hunter syndrome) is an X-linked lysosomal storage disorder caused by a deficiency in the enzyme iduronate-2 sulfatase (I2S), leading to the accumulation of the glycosaminoglycans, affecting multiple organs and systems. Enzyme replacement therapy does not cross the blood brain barrier, limiting results in neurological forms of the disease. Another option of treatment for severe MPS, hematopoietic stem cell transplantation (HSCT) has become the treatment of choice for the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
53
0
2

Year Published

2017
2017
2022
2022

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 42 publications
(57 citation statements)
references
References 29 publications
(43 reference statements)
0
53
0
2
Order By: Relevance
“…Our data show that HSCT is more effective than ERT with improved cognitive outcomes, and if HSCT is performed earlier than at two years of age, cognitive outcomes may be even better. Recently Barth ]et al have reported that a 7-year-old case, who underwent HSCT with umbilical cord blood cells at 70 days of age, showed normal growth in a very healthy condition, improvements in cognitive, language and motor skills, being quite functional although mild signs of dysostosis multiplex and hearing loss [53]. Data from more young HSCT MPS II patients are needed to determine the magnitude of the benefit of early treatment.…”
Section: Discussionmentioning
confidence: 99%
“…Our data show that HSCT is more effective than ERT with improved cognitive outcomes, and if HSCT is performed earlier than at two years of age, cognitive outcomes may be even better. Recently Barth ]et al have reported that a 7-year-old case, who underwent HSCT with umbilical cord blood cells at 70 days of age, showed normal growth in a very healthy condition, improvements in cognitive, language and motor skills, being quite functional although mild signs of dysostosis multiplex and hearing loss [53]. Data from more young HSCT MPS II patients are needed to determine the magnitude of the benefit of early treatment.…”
Section: Discussionmentioning
confidence: 99%
“…Meanwhile, Barth et al. described the general features of the patient and observed through the magnetic resonance imaging (MRI) evaluation, that the spine was normal and X‐rays showed very mild signs of dysostosis multiplex.…”
Section: Discussionmentioning
confidence: 99%
“…5,16 We observed stretching of the stylohyoid processes bilaterally and ectopic/retained teeth, while the other oral structures were normal. Meanwhile, Barth et al 8 described the general features of the patient and observed through the magnetic resonance imaging (MRI) evaluation, that the spine was normal and X-rays showed very mild signs of dysostosis multiplex.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations